“If I don’t write I am not a happy person”: An interview with Margaret McMullan - Negrai, Noémi Ágnes (FOCUS: Papers in English Literary and Cultural Studies, 2010)
The present interview was conducted in December 2010 in the office of the writer as Fulbright professor at the University of Pécs. Q: First, could you talk about your background: place, family, upbringing? MMc: I was born in Newton, Mississippi and we moved in 1969 up to Chicago. It was a big move for me. My mother is from Vienna, Austria and my father is from Lake, Mississippi. They met in Washington D.C. I have always found their relationship very interesting because it is so unusual even in the twenty-first century this kind of couple to me. I went to school at Grinnell College in Iowa and then right after college (four years in Iowa) I had a semester abroad in England, my junior year. I moved to New York even though I had never been there and worked for a magazine, called Glamour Magazine. Basically, I started writing for this magazine by doing interviews. I did that for three and a half years and then quit so that I could write a novel, which I did. It was a bad novel but I finished it. Then I went to graduate school to the University of Arkansas. I didn’t know much about graduate writing programs, I didn’t know they existed but I wanted to study under this man, Jim Whitehead who was from Mississippi too. He helped me a lot. He died a couple of years ago and I have dedicated my last book to him.